Cine MPR interactive multiplanar reformatting of four-dimensional cardiac data using hardware-accelerated texture mapping. - Shekhar, R.
Four-dimensional (4-D) imaging to capture the three-dimensional (3-D) structure and motion of the heart in real time is an emerging trend. We present here our method of interactive multiplanar reformatting (MPR), i.e., the ability to visualize any chosen anatomical cross section of 4-D cardiac images and to change its orientation smoothly while maintaining the original heart motion. Continuous animation to show the time-varying 3-D geometry of the heart and smooth dynamic manipulation of the reformatted planes, as well as large image size (100-300 MB), make MPR challenging. Our solution exploits the hardware acceleration of 3-D texture mapping capability of high-end commercial PC graphics boards. Customization of volume subdivision and caching concepts to periodic cardiac data allows us to use this hardware effectively and efficiently. We are able to visualize and smoothly interact with real-time 3-D ultrasound cardiac images at the desired frame rate (25 Hz). The developed methods are applicable to MPR of one or more 3-D and 4-D medical images, including 4-D cardiac images collected in a gated fashion.
Keywords: 4-D cardiac images; PC graphics boards; Anatomical cross section; Cardiac ultrasound images; Cine MPR; Four-dimensional cardiac data; Frame rate; Gated fashion; Hardware acceleration; Hardware-accelerated texture mapping; Heart motion; Interactive multiplanar reformatting; Original heart motion; Periodic cardiac data; Reformatted planes; Time-varying 3-D heart geometry